Rebreathing during spontaneous and controlled ventilation with T-piece breathing systems: a general solution. - Dorrington, K; Lehane, JR (1989)
A general solution is presented to the problem of finding the degree of rebreathing generated by T-piece breathing systems. The solution is applicable to any ventilatory waveform, dead space volume and tidal volume and is identical for spontaneous and controlled ventilation for any given ventilatory waveform. The method is graphical and its use and understanding require no mathematical skills. However, if an analytical form of the ventilatory waveform is known, the method is easily extended by use of calculus to obtain a precise analytical solution.